Jakość usług edukacyjnych wyższej uczelni jako przedmiot badań marketingowych - dylematy metodologiczne - Hall, Hanna (Quality of University Educational Services as a Subject of Marketing Research - Methodological Dilemmas, 2006)
The aim of the article is to present dilemmas related to the measurement of educational services quality that are offered by schools of higher education considering the student point of view. Moreover, the adaptation barriers of methods are presented that serve the measurement of quality services in business being expressed in the peculiarity of the analysed service and "customer" of higher education.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 294-299